2021
DOI: 10.1302/0301-620x.103b3.bjj-2020-1454.r1
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term outcome of bilateral fragility fractures of the sacrum after bisegmental transsacral stabilization versus spinopelvic fixation

Abstract: Aims Minimally invasive fixation of pelvic fragility fractures is recommended to reduce pain and allow early mobilization. The purpose of this study was to evaluate the outcome of two different stabilization techniques in bilateral fragility fractures of the sacrum (BFFS). Methods A non-randomized, prospective study was carried out in a level 1 trauma centre. BFFS in 61 patients (mean age 80 years (SD 10); four male, 57 female) were treated surgically with bisegmental transsacral stablization (BTS; n = 41) ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Although our study indicated equal use of spinopelvic fixation 6 and sacroiliac screws/transsacral implant fixation 38 , 39 for posterior bilateral displaced sacral fractures (FFP IVb), discriminating radiological factors were not found. Significant pain reduction without complications after operative treatment using percutaneous transiliac-transsacral screws or bilateral sacroiliac screws in the upper sacral segment has been reported 38 , 40 , 41 . Interestingly, even unilateral injuries were recommended bilateral stabilization, probably to avoid fracture progression 35 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Although our study indicated equal use of spinopelvic fixation 6 and sacroiliac screws/transsacral implant fixation 38 , 39 for posterior bilateral displaced sacral fractures (FFP IVb), discriminating radiological factors were not found. Significant pain reduction without complications after operative treatment using percutaneous transiliac-transsacral screws or bilateral sacroiliac screws in the upper sacral segment has been reported 38 , 40 , 41 . Interestingly, even unilateral injuries were recommended bilateral stabilization, probably to avoid fracture progression 35 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this decision meant sacrificing the ability of the CS to describe a transverse fracture component of the sacrum, such as interconnecting bilateral fracture lines, in detail (such a case is summarized with OF4), this sacrifice was deemed acceptable because the impact of the missing information on the decision to pursue conservative versus surgical treatment is unclear. Furthermore, efforts to construct a CS capable of providing categories clearly aligned with surgical procedures to address each fracture type are limited by the lack of evidence for widely varying surgical treatment strategies for OFP [ 10 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The general consensus is that conservative treatment with demand-oriented pain therapy is the first-line therapeutic approach [4]. If conservative therapy fails, surgical fracture stabilization as a second-line therapeutic step is a promising approach [5].…”
Section: Introductionmentioning
confidence: 99%
“…The literature describes a variety of different surgical stabilisation procedures for the treatment of BFFS. In addition to the classic sacroiliac screw fixation with [7] and without [1] cement augmentation, transsacral stabilization [5,8] using extra-long screws or sacral bars and sacroplasty [9,10] is used as minimally invasive procedures. Spinopelvic fixation using open or percutaneous techniques [5] has also been described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation